The degree of availability of the principles of constructivism theory in the health and physical education books for the first secondary grade," the track system", from the health education teachers and supervisors point of view in Al-Riyadh region - Alqaiawi, Manal Abduallah (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate the extent to which the principles of constructivist theory are present in the Health and Physical Education curriculum for the first year of secondary school (Track System) from the perspectives of female teachers and supervisors of Health and Physical Education in Riyadh. The study employed a descriptive-analytical methodology, and the research instrument was a questionnaire comprising 33 indicators based on the constructivist approach, distributed across four domains. The sample consisted of 74 participants, representing all female Health and Physical Education teachers and supervisors in secondary schools within Riyadh. The findings revealed that the overall mean score for the availability of constructivist principles in the curriculum was 3.81, indicating a high degree of presence. Among the domains, the student’s role ranked first with a mean of 3.86, followed by constructivist learning strategies in the curriculum with a mean of 3.84, then the organization of instructional content with a mean of 3.78, and finally, the teacher’s role with a mean of 3.74—all reflecting a high level. Based on these results, the researcher recommended continuing to structure the Health and Physical Education curriculum at the secondary level according to the constructivist learning approach and conducting similar studies in other educational directorates across the Kingdom of Saudi Arabia.